Research Trends in Emotion Regulation of High School Student in Indonesia - Wisma, Nur; Alrefi, Alrefi; Rozaqqyah, Fadhlina; Dewi, Nurmala; Sari, Nadya Permata (JPGI (Jurnal Penelitian Guru Indonesia), 2025)
Emotion regulation is the ability of individuals to manage, control, and express their emotions in a healthy and adaptive manner. This involves the process of monitoring, evaluating, and modifying one's emotional responses in various situations to achieve optimal emotional balance. Therefore, good emotion regulation helps individuals cope with stress, interact with others, and make wise decisions. This research was conducted using a qualitative approach and a literature review method based on twenty journal sources as the focus of the study. The results of this study provide a deeper understanding of the phenomenon of emotion regulation in high school students and help identify influencing factors and strategies to address these issues.